Cashless Society and Financial Literacy in Campus Life to Support Accountable Financial Management - Festi Zulfaturrohmah; Julius Pungky Wasono Widagdo; Kris Brantas Abiprayu; Dheasey Amboningtyas (Economic Education Analysis Journal, 2023)
Rapid technological trends have had a massive have an effect on on Indonesian society, particularly in the use of non-cash transactions. Apart from that, the high growth of internet users is one of the factors in the development of the digital economic system in Indonesia. The Financial Services Authority (OJK) referred to that the usage of digital transactions has also expanded appreciably. This boom in digital transactions is supported via changes in people’s cashless existence, which can be absolutely supported via Bank Indonesia because the valuable financial institution by using launching the National Cashless Movement (GNTT). This motion creates a cashless society organization or frequently known as the “Cashless Society”. This study is covered in quantitative research with the aim of finding out the impact of monetary literacy and lifestyle on the monetary conduct of technology Z in a cashless society. Generation Z at Semarang State University was chosen because the item of studies. The sampling technique in this research uses possibility sampling and the pattern selection in this study makes use of easy random sampling. Calculations to determine the number of samples used the Slovin system. Data collection became completed by means of distributing questionnaires through Google Form and analyzed the usage of Partial Least Square (PLS). The research results show that cashless transactions have not been able to reduce the amount of cash needed by generation Z or Semarang State University students. So it has not been possible to reduce the amount of cash circulated indirectly.